Analisis Kompetensi Profesional Guru Di Sekolah Menengah Pertama - ., Irmawati (Program Studi Administrsi Pendidikan Program Pascasarjana UNM, 2013)
This study aims at examining the description on the professional competence of teachers which includes the development of school-based curriculum, the mastery of learning material, management of learning program, classroom management and the use of media and sources of learning at SMP Islam Al-Azhar 24 Makassar. The location of the study was centered at SMP Islam Al-Azhar 24 Makassar. The type of research of the study was descriptive qualitative research. The data sources were selected purposively. The techniques used in collecting the data were observation, interview, and documentation. The data then were analyzed using descriptive qualitative method by conducting data reduction, data presentation and data verification. The results of the study concluded that (i) the development of school-based curriculum had been conducted standard and basic competence as well, (ii) the mastery of learning material, teachers had fulfilled the standard, (iii) the management of learning program had been conducted well, (iv) classroom managementÂ was conducted well, and (v) the implementation of media and sources of learning were used well and appropriate to the needs of learning at SMP Islam Al-Azhar 24 Makassar. Â Keywords: Proffesional Competence of Teachers.